Assessing the impact of lime on chromium migration in soil caused by basic chromium sulfate in tannery - Song, Li-Jie (Environmental technology, 2023)
Chromium (Cr) pollution is the primary pollution problem of the soil in tannery. However, the effect of tanning chemicals on Cr migration in soil has not been clearly elucidated. Column leaching tests were designed in this study to reveal the transport and transformation of Cr from basic chromium sulfate (BCS) into soil and the effects of lime on Cr migration and transformation. The results showed that BCS was mainly leached out in the state of Cr(VI) after entering the soil, and the Cr concentration in leachate decreased with the increase of the bulking thickness of the BCS. Compared with the soil absent of lime, the concentration of total Cr in the leachate from soil with lime decreased by 8.80-88.1%. The proportions of Cr in the residual fraction were generally increased in the soil with lime, whereas other fractions were decreased. The presence of lime can reduce the migration and toxicity of BCS in soil to a certain extent. The analysis of soil bacterial community showed that the relative abundance of Proteobacteria increased significantly with the exposure to BCS and the Burkholderiaceae was the dominant bacteria family in the BCS contaminated soil. Understanding the mobility of BCS and lime and the bacterial community in BCS contaminated soil is conducive to the risk assessment of the tannery site